2007
DOI: 10.1093/molbev/msm103
|View full text |Cite
|
Sign up to set email alerts
|

The Genesis and Spread of Reassortment Human Influenza A/H3N2 Viruses Conferring Adamantane Resistance

Abstract: A dramatic rise in the frequency of resistance to adamantane drugs by influenza A (H3N2) viruses has occurred in recent years -- from approximately 2% to approximately 90% in multiple countries worldwide-and associated with a single S31N amino acid replacement in the viral matrix M2 protein. To explore the emergence and spread of these adamantane resistant viruses we performed a phylogenetic analysis of recently sampled complete A/H3N2 genome sequences. Strikingly, all adamantane resistant viruses belonged to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
172
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(189 citation statements)
references
References 30 publications
15
172
0
2
Order By: Relevance
“…As most of these resistance strains have the same substitution (Ser31Asn for the M2 gene of A/H3N2 viruses) and antiviral agents are not commonly used in this region, a common origin for these viruses is a strong possibility 23 . In agreement to previously published data, 24 these findings suggest that these resistant variants could have arisen in the absence of any antiviral selective pressure, or if they have a common origin in places where antiviral agents are used, they must have an advantage for their maintenance even in the absence of these agents that contributed to their migration, global distribution and maintenance over a 3 year period.…”
Section: Resultssupporting
confidence: 91%
“…As most of these resistance strains have the same substitution (Ser31Asn for the M2 gene of A/H3N2 viruses) and antiviral agents are not commonly used in this region, a common origin for these viruses is a strong possibility 23 . In agreement to previously published data, 24 these findings suggest that these resistant variants could have arisen in the absence of any antiviral selective pressure, or if they have a common origin in places where antiviral agents are used, they must have an advantage for their maintenance even in the absence of these agents that contributed to their migration, global distribution and maintenance over a 3 year period.…”
Section: Resultssupporting
confidence: 91%
“…Indeed, large-scale sequencing of transmissible viruses isolated as early as 1918 showed that mutations to pore-lining residues are allowed only within the first turn of the transmembrane (TM) helix at positions 26, 27, and 31 (10). S31N has long been the predominant amantadine-resistant mutation in M2 (11)(12)(13)(14). It predominated in 98-100% of the transmissible amantadineresistant H1N1, H5N1, and H3N2 strains isolated from humans, birds, and swine in the past decade.…”
Section: M2-s31n Inhibitormentioning
confidence: 99%
“…1(A)]. S31N has long been the dominant amantadine-resistant mutation in M2, [46][47][48][49] accounting for 98-100%…”
Section: Natural and Artificial Sequence Variants Of M2mentioning
confidence: 99%